2018
DOI: 10.1002/ppul.24046
|View full text |Cite
|
Sign up to set email alerts
|

Airway dimensions from fetal life to adolescence—A literature overview

Abstract: This work revealed a large heterogeneity of studies providing data on pediatric airway dimensions, making it impossible to compare, or assemble them to normograms for clinical use. Comprehensive studies in large population of children are needed to provide full range nomograms on pediatric airway dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…Despite these limitations, Kemper et al used this data to mathematically assess the appropriateness of seven pediatric ETT brands, and found that none allowed safe ETT placement using five intubation depth strategies 24 . A subsequent systematic literature review concluded that the large heterogeneity of studies made it impossible to assemble them to nomograms for clinical use 25,26 . The purpose of our study was to 1) define the length of the subglottis and trachea in a large number of boys and girls, with normal and abnormal airways, from birth to adolescence broken into small age ranges, measured during spontaneous ventilation without airway obstruction, and analyzed in relation to age, body weight, height, and chest height; 2) use these measurements to predict a safe intubation depth to prevent subglottic cuff placement and endobronchial intubation.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these limitations, Kemper et al used this data to mathematically assess the appropriateness of seven pediatric ETT brands, and found that none allowed safe ETT placement using five intubation depth strategies 24 . A subsequent systematic literature review concluded that the large heterogeneity of studies made it impossible to assemble them to nomograms for clinical use 25,26 . The purpose of our study was to 1) define the length of the subglottis and trachea in a large number of boys and girls, with normal and abnormal airways, from birth to adolescence broken into small age ranges, measured during spontaneous ventilation without airway obstruction, and analyzed in relation to age, body weight, height, and chest height; 2) use these measurements to predict a safe intubation depth to prevent subglottic cuff placement and endobronchial intubation.…”
Section: Introductionmentioning
confidence: 99%
“…Literature presenting dimensional data on tracheal diameters and lengths, cricoid diameters, subglottic and glottic dimensions, LMB and RMB data in pediatric patients was also found. Research studies measuring glottic and subglottic dimensions were excluded from graphs due to a major incongruence in definition, imprecise information about the site of measurement and their dependency on functional effects (spontaneous breathing vs muscle paralysis) . Diameters were measured as “ap” and transverse (lateral) and given for mid, proximal, distal trachea, and bronchi, respectively (Figures , and ; Table S2‐S6).…”
Section: Resultsmentioning
confidence: 99%
“…We further did not assess the clinical consequences of the size variations (i.e., resistance) in a physical model with anatomic variations or in a clinical setting. Most importantly, it is not clear what degree of variation really presents a clinical problem, because, other than in children [21], there are no data on the anatomic parameters in adults that would predispose them for given DLT sizes. Being beyond the scope of this work, the ultimate clinical goal maybe would be to obtain data about the rate of necessary tube changes when following different guidelines for tube size selection.…”
Section: Discussionmentioning
confidence: 99%